Central exclusive diffractive production of pp[bar] pairs in proton-proton collisions at high energies - Lebiedowicz, Piotr; Nachtmann, Otto; Szczurek, Antoni (Physical review, 2018)
We consider the central exclusive production of the p¯p in the continuum and via resonances in proton-proton collisions at high energies. We discuss the diffractive mechanism calculated within the tensor-Pomeron approach including Pomeron, Odderon, and Reggeon exchanges. The theoretical results are discussed in the context of existing WA102 and Intersecting Storage Rings experimental data, and predictions for planned or current experiments at the Relativistic Heavy Ion Collider and the LHC are presented. The distribution in ydiff, the rapidity distance between the proton and antiproton, is particularly interesting. We find a dip at ydiff=0 for the p¯p production, in contrast to the π+π− and K+K− production. We predict also the p¯p invariant-mass distribution to be less steep than for the pairs of pseudoscalar mesons. We argue that these specific differences for the p¯p production with respect to the pseudoscalar meson pair production can be attributed to the proper treatment of the spin of produced particles. We discuss asymmetries that are due to the interference of C=+1 and C=−1 amplitudes of p¯p production. We have also calculated the cross section for the pp→ppΛ¯Λ reaction. Here, the cross section is smaller, but the characteristic feature for dσ/dydiff is predicted to be similar to p¯p production. The presence of resonances in the p¯p channel may destroy the dip at ydiff=0. This opens the possibility to study diffractively produced resonances. We discuss the observables suited for this purpose.
Im Titel steht der Buchstabe "p" mit einem Oberstrich
Gesehen am 25.02.2020